PET ATTACHMENT AND STRESS LEVELS AMONG PRECLINICAL MEDICAL STUDENTS - Santosa, Mariani; Hardi, Nicholas; Jessica, Cicilia (Universitas Airlangga, 2025)
Introduction: Medical students are considered an academic group highly prone to stress, with prevalence rates ranging from 28.5% to 78%. Human-Animal Interaction (HAI) has been shown in several studies to correlate positively with stress reduction. A 2021 Rakuten Insight survey across 12 Eastern and Southern Asian countries reported that 41% of respondents kept pets to alleviate sadness and stress, while 36% cited companionship. Pets are seen as valuable emotional resources and adaptive tools for managing stress. Aims: This cross-sectional study was conducted to assess the levels of stress experienced by preclinical medical students. The study specifically aimed to explore the relationship between the degree of attachment these students have to their pets and their reported stress levels. Methods: A total of 100 preclinical students took part in this study. The pet attachment scores and stress levels were assessed using standard questionnaires. Data from this study were analyzed using a one-way ANOVA test and Post Hoc analysis. Results: The average pet attachment score in this study was 49.73. The pet attachment scores were higher in female participants and participants who kept their pets for over nine years. Most respondents experienced moderate stress levels (81%). Significant differences were found in the pet attachment score to mild-moderate stress levels (p = 0.001). Conclusion: The results obtained from this study lend support to the hypothesis that attachment to pets has a positive impact on stress levels.